Use of Courgette and Added Citrus Fruit for Jam Production - Przybylska, Sylwia; Przybylski, Damian; Lindorf, Krzysztof (Wykorzystanie cukinii i dodatku owoców cytrusowych do produkcji dżemów, 2022)
Jams as sweet spreads occupy an important place among the processed products on offer. Despite the wide range of such products, courgette jams are absent. This vegetable, due to its sensory properties: light colour and delicate taste and smell, which can be easily modified with the addition of other components, seems to be a suitable raw material for their production. The aim of this study was to develop jams based on courgetti mixed with 30% of citrus fruits and to assess their impact on the quality of the product. The jams were produced in two versions: traditional with the addition of sugar and “light” with its substitute – xylitol. Color, pH, total extract, total acidity and content of bioactive compounds were determined in them. Sensory evaluation was carried out on a 5-point scale and their general acceptability on a 9-point hedonic scale. Studies have shown that the addition of lime, lemon and orange to the production of courgette jams allowed to obtain products with the best sensory properties and high nutritional value. For comparison, jams with the addition of grapefruit were distinguished by lower acceptability due to the perceptible bitterness of their taste.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 186-204